Increasing The Motivation To Learn English For Students Of The Boarding School Of Smk Jawahirul Ulum Jabon Sidoarjo By Using An Android Application - Shofi, Millatus; Sari, Tungga Purnama (Program Studi Pendidikan Agama Islam, 2023)
This research aims to evaluate the effectiveness of using Android applications in increasing motivation to learn English among students at Jawahirul Ulum Vocational School, Jabon Sidoarjo. Using a pretest-posttest control group design, this research involved two groups of students: an experimental group who used the Android application and a control group who did not use the application. The results showed that the experimental group experienced significant improvements in motivation and English language proficiency compared to the control group. This increase in motivation and proficiency can be explained through several educational theories, including Self-Determination Theory which emphasizes the importance of autonomy and competence, and Engagement Theory which underlines the importance of active involvement in the learning process. Android apps provide interactive, personalized, and flexible learning, allowing students to learn at their own pace and interests. Additionally, the app offers a cost-efficient learning solution, providing broad access to quality educational resources without burdening school budgets. The results of this research support the use of digital technology in education to create a more adaptive, interesting and effective learning environment. The integration of Android applications in the English learning curriculum not only increases students' motivation and learning outcomes, but also prepares them to face future challenges better. These findings demonstrate the enormous potential of technology in transforming traditional educational practices and improving the overall quality of education.